Tirkah Negotiation: A Social Interpretation of Pension Salaries on Inheritance Practices in Situbondo District - Ishaq; Khoirul Hadi Al Asyari; Moh. Wasik; Moh. Faiq Rafiul Anshary; sugianto; Muhammad Kadafi Bashori (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines how the Situbondo Muslim community negotiates the meaning of tirkah (inheritance property) in the context of pension salaries, which administratively can only be disbursed by legal spouses, while other heirs often do not get equal access. Problems arise when inheritance in the form of pension salaries creates tension because there is no standardized agreement on its status as part of the tirkah. The purpose of this study is to understand how social interpretations of pension salaries are shaped, negotiated and enacted in local inheritance practices. This research used a qualitative approach with ethnographic type, involving ten informants consisting of civil servants, ulama, bureaucrats, and intellectual youth. Data collection techniques were conducted through observation, in-depth interviews, and documentation, using purposive sampling techniques. Data analysis used the Miles and Huberman interactive model, with a descriptive approach. The results show that pension funds are understood differently in Islamic law and positive law; Islam considers it part of tirkah if it comes from the right of the heir, while positive law stipulates it as the right of the legal spouse. The views of contemporary scholars also vary; some consider it inheritance, while others see it as a grant. In Situbondo, the community interprets pension funds socially through family deliberation, emphasizing justice and benefit, so the distribution of inheritance is flexible and contextual